HOUSE-BUILDING ANALYSIS WHEN USING ADDITIVE TECHNOLOGIES: CLASSIFICATION, ADVANTAGES AND DISADVANTAGES - Pahomova, Ekatarina Gennadievna; Monastyrev, Pavel Vladislavovich; Mishchenko, Elena Sergeevna; Yezerskiy, Valery Alexandrovich; Ivanov, Ivan Aleksandrovich; Balthazar, Azaoui Doubla (Journal of Applied Engineering Science, 2019)
The construction industry is evolving in the field of development and implementation of an information modeling approach for buildings. At present, digital building models are being transferred to the construction industry, where 3D printers are used to erect buildings. By extrusion theyapply concrete mixture layer by layer along the limit contour of the building structure, thereby making building structures of the building or “printing” the building.The article discusses the principle of construction when using additive technologies. It also analyzes the existing technologies for “printing” buildings and it considers the advantages and disadvantages of this technology. Besides, the work gives a classification of building technologies and the exterior walls of the constructed buildings using 3D printers.
Keywords: construction industry; Extrusion; additive technology; 3D construction printer; information and digital technologies